(untitled) (Journal of actual problems of jurisprudence, 2019)
Juvenile delinquency is due to the mutual influence of negative environmental factors and personality of the minor. Juvenile delinquency is primarily determined by the individual characteristics of the offender, associated with its certain biological, psychological and mental changes in structure of their personality. Age is due to a certain level of strength, intelligence, instincts, and even «physical» possibilities of committing certain crimes. Key words: minor crime, juvenile delinquency, identification of a juvenile offender.